PENINGKATAN PROFITABILITAS PADA INDUSTRI PERBANKAN GO-PUBLIK DI INDONESIA - Santoso, Adi (MediaTrend, 2016)
The aim at the study to examine and analyze the impact growth of profitability through its capital adequacy ratio, operating expense to operating income, loan to deposit ratio andÂ  non perfoming loan in the banking industry go public in indonesia. This study used 29 banking companies in indonesia were selected as sample. The results show that operating expense to operating income and loan to deposit ratio have significantly effect to return on asset while the capital adequacy ratio,and non perfoming loan not significantly effect to return on asset. Capital adequacy ratio, operating expense to operating income, loan to deposit ratio and non perfoming loan not significantly effect to return on equity. While for variable stock returns are significantly influenced only by the capital adequacy ratio, operating expense to operating income, loan to deposit ratio, return on asset andÂ  return on equity while non perfoming loan not significantly effect to stock returns